Histopathology aspects and fibrosis evaluation of bovine naturally infected livers by Fasciola hepatica - Trivilin, Leonardo Oliveira; de Sousa, Dyeime Ribeiro; Nunes, Louisiane de Carvalho; Rocha, Noeme de Sousa [UNESP]; Martins, Isabella Vilhena Freire (My University, 2014)
Fasciolosis is a zoonotic disease that infects especially ruminants and the liver damages in chronic infection caused by the parasite are very severe. The aim of this study was to evaluate the histopathological findings in liver of cattle naturally infected with Fasciola hepatica, as well as propose a classification of liver damage caused by this disease based on the chronic inflammation and fibrosis. Were used fragments of the right lobe and left of one hundred livers the cattle. Those fragments were subjected to histological processing and staining with haematoxylin-eosin and Masson's trichrome. Assigned to graduate I to III for the classification of lesions according to the intensity of the inflammatory and fibrotic changes. The lesions more prevalent were biliary duct proliferation, mononuclear cell infiltration, arteriosclerosis, and periportal and periductal fibrosis. Fibrotic lesions were more intense than the inflammatory and 45% of the samples belonged to category II, followed by 39% in category I and 16% in category III. The proposed categorization of pathological liver injury in chronic fasciolosis in naturally infected cattle proved is a valuable method of microscopic evaluation, since it allows determining the evolution of this disease.
Keywords: Cattle; Fasciola hepatica; Fascioliasis; Liver